2018
DOI: 10.2478/sgem-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and settlement evaluation of an end-bearing granular pile with non-linear deformation modulus

Abstract: Ground improvement with granular piles increases the load-carrying capacity, reduces the settlement of foundations built on the reinforced ground and is also a good alternative to concrete pile. Granular piles or stone columns are composed of granular material, such as crushed stone or coarse dense sand. An analytical approach based on the continuum approach is presented for the non-linear behaviour of the granular pile. The formulation for pile element displacement is done considering the non-homogeneity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…Szypcio [22] presented the problem of plastic yielding at the head of a single column head and soil in the surroundings. The settlement influence factor for an end-bearing granular pile decreases with an increase in the bearing stratum's relative stiffness, as concluded by Sharma and Gupta [23].…”
Section: Literature Reviewsupporting
confidence: 56%
“…Szypcio [22] presented the problem of plastic yielding at the head of a single column head and soil in the surroundings. The settlement influence factor for an end-bearing granular pile decreases with an increase in the bearing stratum's relative stiffness, as concluded by Sharma and Gupta [23].…”
Section: Literature Reviewsupporting
confidence: 56%
“…In general, the deformation modulus has been analyzed and usually obtained by the existing theoretical methods and stress-strain curves. For example, Kiran et al [15] proposed a method to calculate the deformation modulus of a granular pile by an in-situ load test, and Sharma and Gupta [16] found that the granular pile has non-uniform settlement according to the non-linear deformation modulus. In the laboratory, the deformation modulus of granular materials is usually obtained by compression experiments.…”
Section: Introductionmentioning
confidence: 99%